Sosyo-Ekonomik Yapının Rekreasyonel Eğilim ve Talepler Üzerine EtkisiBartın Kenti Örneği - Talay, İlkden; Kaya, Fadime; Belkayali, Nur (Cografi Bilimler Dergisi, 2010)
This study was conducted to investigate the impact of people's socio-economic characteristics to recreational trends and demand, to increase the quality of urban recreation areas and to overture for the satisfaction of requests by determining the recreational trends and demands of the people of the city. Bartın is located in the northwest of the Anatolian city and chosen as the sample area. In the context of study, primarily Bartın’s recreation opportunities are examined and, areas which used for recreation or have recreation potential in urban and around urban environment are identified. Then, survey was conducted for the people of the city with the aim of determination of recreational trends and demands and associated with socio-economic structure., The participation of city population to the recreational activities, recreation type and field preference, relationships with these fields, satisfaction status from the conditions and demands were displayed with survey findings, observations and statistical analysis and also the relationship between people's socio-economic structures, properties of recreation areas and the recreational trends and demands were illustrated
Keywords: Geography (General); G1-922; recreational demand; Rekreasyonel eğilim; Rekreasyonel talep; Sosyo-ekonomik yapı; Bartın; socio-economic structure; Recreational trend; Recreational demand; Socio-economic structure; Bartın city; recreational trend; bartın city; 11. Sustainability